Karakteristik sosial demografi dan konsumsi zat besi pada ibu hamil berdasarkan data Studi Diet Total (SDT) tahun 2014 di Indonesia - Safrullah Amir; Susetyowati Susetyowati; Arta Farmawati (Jurnal Gizi Klinik Indonesia, 2018)
Background: Pregnant women are the group most vulnerable to iron deficiency anemia. This occurs as a consequence of a significantly increased demand for iron intake during pregnancy. The efforts of pregnant women to compensate for the increased need of iron depend on various sociodemographic characteristics.Objective: To analyze the relationship between sociodemographic characteristics and iron consumption of pregnant women in Indonesia.Method: This research is observational study design with cross-sectional approach using secondary data of the Total Dietary Study (SDT) year 2014. A total of 644 pregnant women inform the SDT study who met our inclusion and exclusion criteria were assessed for their level of consumption using 24-hour dietary recall method. Data were then processed using Nutrisurvey software and Indonesian Food Composition Table (TKPI) to estimate the consumption of iron. Analysis was conducted using Mann-Whitney and Kruskal-Wallis tests by including various social demographic characteristics in pregnant women.Results: The results of this study found that level of education, employment status, economic status, and residence of pregnant women are significantly related to iron consumption (p<0.05).Conclusion: Pregnant women with high education, working status, middle to upper economic status, and living in urban areas have better iron consumption.